PARTISIPASI MASYARAKAT DAN TINGKAT KEBUGARAN JASMANI BAGIAN DARI PEMBANGUNAN OLAHRAGA KABUPATEN WONOGIRI - NATALIA, DESI (Media Ilmu Keolahragaan Indonesia, 2016)
Development is an effort purposed at achieving better conditions. In the sector of sports, development not only based on the medals procuration in the competition multievent, but public paticipation in exercise and also the level of physical fitness is part of the Sport Development Index (SDI). The purpose of this study to determine the level of public participation and the level of physical fitness society of Wonogiri. This study is evaluation sport development by using a mixture of quantitative and qualitative evaluation context. Data collection technique used observation, questionnaires, Multistage Fitness Test (MFT), and documents. The subject of this study are consisted of the child (7-12 years) 30 people, adolescence (13-17 years) 30 people and adults (18-40 years) 30 people. each age group consisted of 15 men and 15 women. The subjects filled out questionnaires public participation in the sport before Multistage Fitness Test (MFT) to measure the level of physical fitness. Based on the result of study, it can be concluded that the public participation index of 0, 237 and physical fitness index of 0.315. If the terms of the norm Sport Development Index (SDI) is in the range from 0.000 to 0.499, which means public participation and level of physical fitness society of Wonogiri Regency that are in the low category.Â